2014
DOI: 10.1155/2014/589538
|View full text |Cite
|
Sign up to set email alerts
|

Functional Evaluation in High Energy (Schatzker Type V and Type VI) Tibial Plateau Fractures Treated by Open Reduction and Internal Fixation

Abstract: Objective. To review functional outcome in high energy tibial plateau fractures treated by plating. Design. Retrospective analysis. Material and Methods. Sixty-five patients with Schatzker type V and type VI tibial plateau fractures treated with open reduction and internal fixation using plates were included in the study. The functional evaluation of the patients was carried out with Oxford knee scoring. Results. Fifty-four cases (83%) had Oxford knee score between 40 and 48. Seven (10.7%) had score between 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 25 publications
1
20
0
1
Order By: Relevance
“…In a study by Khatri et al, superficial wound infection was seen in 9.2% patients while deep infection was seen in 4.6% of patients. 24 Barei et al, had reported superficial infection in 5.4% patients and deep wound infections 3.6% patients.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In a study by Khatri et al, superficial wound infection was seen in 9.2% patients while deep infection was seen in 4.6% of patients. 24 Barei et al, had reported superficial infection in 5.4% patients and deep wound infections 3.6% patients.…”
Section: Discussionmentioning
confidence: 92%
“…In a study of 65 cases of type V and type VI fractures by Khatri et al, 54 patients (83%) had excellent result. 24 A study by Prasad et al has observed excellent oxford knee score in 40% of their patients treated with dual incision and dual plate. 23 The most dreadful complication associated with the management of tibial plateau fractures is infection.…”
Section: Discussionmentioning
confidence: 98%
“…Compared with CT, AP radiography has a lower detection rate of proximal fibula fracture in associated with tibial plateau fractures. [18][19][20][21] Our findings demonstrated distinct fracture characteristics of these combined high-energy tibial plateau and fibula fractures owing to the use of a combination of the Schatzker's and three-column classification systems.…”
Section: Discussionmentioning
confidence: 94%
“…[13][14][15] As previously reported, tibial plateau fractures develop as a result of varus or valgus forces, axial (compressive) force, or both. [16][17][18] The proximal tibiofibular joint, which includes the lateral collateral ligament, biceps femoris tendon, fibular sesamoid bone ligament, and arcuate ligament, provides a stable articulation between the lateral tibial condyle and the fibular head. Therefore, the displacement of the proximal fibula segment eliminates its support of the lateral tibial plateau and potentially complicates fracture reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Dual plating for complex bicondylar tibial plateau (Schatzker type V and VI) fractures has gained popularity because of its optimal functional outcome and patient compliance. Many studies have supported the use of this technique in complex bicondylar tibial plateau citing excellent functional outcomes and better patient compliance [15,18,19] . But still this modality is in evolving phase to improve patient outcome.…”
Section: Introductionmentioning
confidence: 99%